South Korea’s Growth Trajectory: High Performance with a Profit Share Below One-Third in Emerging and Advanced Economies - Villemeur, Alain (Journal of Emerging Markets and Management, 2025)
What is the growth model of emerging economies striving to develop rapidly to become advanced economies? South Korea is the only poor economy, sixty years ago, to have become an emerging economy and then an advanced economy. For advanced economies since 1961, a new growth and distribution model has been proposed to explain the increase in the profit share of income and, simultaneously, the significant decline in GDP growth and labor productivity. Macroeconomic developments in South Korea are analyzed in detail, with standardized data available since 1975. It appears that high GDP and productivity growth are also associated with a low profit share, less than one-third over the long period from 1975 to 2019, as was the case for advanced economies during the Golden Age of Capitalism. South Korea is also the only advanced economy since the 2008 financial crisis to maintain high GDP and productivity growth. The considered growth and distribution model provides important insights both for advanced economies and for an emerging economy becoming an advanced economy like South Korea. For rapid economic growth, the key factors appear to be a low profit share, well below one-third, income-led growth, reduced inequality, and high R&D spending.